PROBLEMS OF INDIVIDUALIZING THE PEDAGOGICAL EDUCATION PROCESS (Global Conference on Multidisciplinary Research and Innovation, 2026)
The modern requirements placed on the education system are increasingly enhancing the importance of individualization as a promising direction in its development. Because individualization makes it possible to create the necessary conditions for the development of human capital — one of the main tasks of educational practice — as well as for consciously understanding one’s activities and demonstrating one’s potential.